Bronchiolitis Obliterans Organising Pneumonia (BOOP) in a lung cancer patient after lobectomy - Yan, S.W.; Wong, C.F.; Wong, P.C.; Cheung, C.F. (Monaldi Archives for Chest Disease, 2005)
A 79 year-old patient with lung cancer underwent a standard thoracotomy and lobectomy. Postoperatively, he developed low-grade fever and dyspnoea. Chest X-rays showed progressive lung infiltrates, which was subsequently diagnosed to be Bronchiolitis Obliterans Organizing Pneumonia (BOOP) by transbronchial lung biopsy. He responded well to corticosteroid therapy. The case report is followed by a brief discussion on BOOP in association with lung cancer and thoracotomy.